2019
DOI: 10.21608/ejhc.2019.36696
|View full text |Cite
|
Sign up to set email alerts
|

Mothers ' knowledge and Practices toward Their Children Suffering from Juvenile Diabetes: an Assessment Study

Abstract: Background: Juvenile diabetes remains one of the most complex chronic diseases in childhood. Adolescents and those of lower socio-economic status are at higher risk for poorer metabolic control and difficulties with psychosocial well-being. Juvenile diabetes can be associated with adverse effects on cognition during childhood and adolescence. Caring for children with Juvenile diabetes is typically the role of the mother. Mother must pay special attention to the promotion of good eating habits, stimulate physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…The current study illustrated that there was a positive correlation between total score of the mother's knowledge about type 1 diabetes in children and total score of the mothers' practices. This result was consistent with Hussien et al,(2019) who conducted a study about "Mothers' Knowledge and Practices toward their Children Suffering from Juvenile Diabetes: an Assessment Study", it was found that Effect of Mothers' Care Adherence on Control of type 1 Diabetes Mellitus Among their Children there was a positive correlation between the total knowledge of the studied mothers about juvenile diabetes and their total reported practices.…”
Section: Part Iv: Pearson Correlation Between Studied Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…The current study illustrated that there was a positive correlation between total score of the mother's knowledge about type 1 diabetes in children and total score of the mothers' practices. This result was consistent with Hussien et al,(2019) who conducted a study about "Mothers' Knowledge and Practices toward their Children Suffering from Juvenile Diabetes: an Assessment Study", it was found that Effect of Mothers' Care Adherence on Control of type 1 Diabetes Mellitus Among their Children there was a positive correlation between the total knowledge of the studied mothers about juvenile diabetes and their total reported practices.…”
Section: Part Iv: Pearson Correlation Between Studied Variablessupporting
confidence: 89%
“…From the researcher's perspective, this could be attributed to the positive effect of education program, good preparation of the mothers before the program; mothers were enthusiastic to know everything about diabetes, oral presentations, group discussion, feedbacks, explanatory booklets and videos, as well as facilitating effective online communication with the mothers. Also this result was inconsistent with Hussien et al, (2019) who conducted a study about " Mothers ' knowledge and Practices toward Their Children Suffering from Juvenile Diabetes: an Assessment Study", it was found that about two third from the diabetic children's mothers had unsatisfactory total knowledge score about care of their children.…”
Section: Diabetes On Pre and Posttestmentioning
confidence: 65%